Treatment of small coronary arteries with a paclitaxel-coated balloon catheter in the PEPCAD I study: are lesions clinically stable from 12 to 36 months? - Unverdorben, Martin; Kleber, Franz Xaver; Heuer, Hubertus; Figulla, Hans-Reiner; Vallbracht, Christian; Leschke, Matthias; Cremers, Bodo; Hardt, Stefan; Buerke, Michael; Ackermann, Hanns; Boxberger, Michael; Degenhardt, Ralf; et al. (EuroIntervention, 2013)
Drug-coated balloon, small coronary vessels, DCB only
Gesehen am 17.02.2022